The cognitive and behavioral correlates of functional status in patients with frontotemporal dementia: A pilot study - Chatzidimitriou, Electra; Ioannidis, Panagiotis; Moraitou, Despina; Konstantinopoulou, Eleni; Aretouli, Eleni (Frontiers in Human Neuroscience, 2023)
Objective: Frontotemporal dementia (FTD) impinges significantly on cognition, behavior, and everyday functioning. Goal of the present study is the detailed description of behavioral disturbances and functional limitations, as well as the investigation of associations between cognition, behavior, and functional impairment among FTD patients. Given the importance of maintaining a satisfying functional status as long as possible, this study also aims to identify the cognitive correlates of compensatory strategy use in this clinical group. Methods: A total of 13 patients diagnosed with FTD (behavioral variant FTD=9, non-fluent variant primary progressive aphasia=3, semantic dementia=1) were administrated a broad range of neuropsychological tests for the assessment of different cognitive abilities. Behavioral symptomatology and performance on everyday activities were rated with informant-based measures. Descriptive statistics were used for the delineation of behavioral and functional patterns, whereas stepwise multiple regression analyses were performed to identify associations between cognition, behavior, and functional status. Results: Negative symptoms, especially apathy, were found to predominate in the behavior of FTD patients. Instrumental tasks, such as housework and leisure activities, appeared to be the most impaired functional domains. Working memory was the strongest cognitive correlate of performance across various domains of everyday functioning, whereas working memory along with short-term verbal memory accounted for a great proportion of variance in compensatory strategy use. Behavioral disturbances and especially negative symptoms were also found to contribute significantly to functional impairment in FTD. Conclusions: Executive dysfunction, as well as behavioral disturbances contribute significantly to functional disability in FTD. Early interventions tailored at these domains may have the potential to improve functional outcomes and delay the rate of functional decline among FTD patients.